Ørnen flyr – om Stil I i Norden - Magnus, Bente (Hikuin, 2002)
The Eagle flies – on Style I in Scandinavia By Bente Magnus During excavations in 1998 for a new section of the motorway E 4 through Väderstad, Östergötland, Sweden a unique square-headed relief brooch came to light in what was interpreted as a ritual area in the vicinity of Abbetorp. The brooch, which is 11.4 cm long and 6.8 cm across the headplate, is made of gilded silver and decorated with Style I animal figures in high relief and further embellished with silver and niello. It is one of the most beautiful relief brooches found in Sweden in the twentieth century. The brooch belongs to the category of ridged foot relief brooches, with the footplate divided along the middle by a bar like the ridge of a roof. In spite of this feature the artisan provided the brooch with a unique and elaborate catch-plate for the pin in the shape of a flying bird of prey attached to the back of the footplate. The Abbetorp brooch provides a starting point for a discussion of the first Germanic animal style, Style I, its cultural background and how it was used by the Germanic societies.